Modification of tissue fatty acid composition in Murray cod (Maccullochella peelii peelii, Mitchell) resulting from a shift from vegetable oil diets to a fish oil diet. - Giovanni Turchini; David Francis; S De Silva (2006)
The dynamics of fatty acid composition modifications were examined in tissues of Murray cod fed diets containing fish oil (FO), canola oil (CO) and linseed oil (LO) for a 25-week period and subsequently transferred to a FO (finishing/wash-out) diet for a further 16 weeks. At the commencement of the wash-out period, following 25 weeks of vegetable oil substitution diets, the fatty acid compositions of Murray cod fillets were reflective of the respective diets. After transfer to the FO diet, differences decreased in quantity and in numerousness, resulting in a revert to the FO fatty acid composition. Changes in percentages of the fatty acids and total accumulation in the fillet could be described by exponential equations and demonstrated that major modifications occurred in the first days of the finishing period. A dilution model was tested to predict fatty acid composition. In spite of a general reliability of the model ( Y =0.9234 X +0.4260, R 2 =0.957, P <0.001, where X is the predicted percentage of fatty acid; Y the observed percentage of fatty acid), in some instances the regression comparing observed and predicted values was markedly different from the line of equity, indicating that the rate of change was higher than predicted (i.e. Y =0.4205 X +1.191, R 2 =0.974, P<0.001, where X is the predicted percentage of α-linolenic acid; Y the observed percentage of α-linolenic acid). Ultimately, using the coefficient of distance ( D ), it was shown that the fatty acid composition of fish previously fed the vegetable oil diets returned to the average variability of the fillet fatty acid composition of Murray cod after 70 or 97 days (LO and CO respectively).